Product Packaging Design as The Basis of Product Purchase Decision - Jiaying Gao; Marlon Rael Astillero (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Market homogenization leads to fierce competition in the tea market. In recent years, with the rise of “green health” and the deep-rooted concept of “innovation”. Tea packaging design innovation has become a hot spot for research in the tea industry. The continuous upgrading of tea market demand has shown vigorous vitality and energy. The study aims to examine the research on the influence of Chinese tea packaging design on product purchasing decisions and analyze its importance and influencing factors. Further, strengthen the sustainable development of tea packaging design in Yanhu District, Shanxi Province, China. Theoretical analysis was conducted of tea cognitive attitudes, tea culture, tea packaging design, and purchase decision behavior. The final online questionnaire was distributed to 321 respondents in the Yanhu District. Empirical research results indicate that all three dimensions of tea packaging design factors positively influence, but the degree of influence varies. Tea products can be enhanced through packaging design to influence purchasing decisions. Ultimately, it can explore the packaging effect of tea products and add value to the connotation of tea products and meet the multi-level demand of consumers for tea products.